Eastern Africa Root Crops Research Network (EARRNET) legacy; performance report: 20042007 - Ntawuruhunga, Pheneas; Okidi, J. (International Institute of Tropical Agriculture, 2010)
During the two 5-year consecutives phases ( 1994–1998 and 1999–2003) EARRNET operated considerably among the national cassava research programs of Burundi, Democratic Republic of Congo, Kenya, Madagascar, Rwanda, and Uganda. After 2000, the network expanded significantly with activities in Southern Sudan and Ethiopia with a mission to transform cassava into a broad-based commercial commodity for sustained food security, poverty alleviation, and income generation through integrated regional production, utilization, marketing, and trade. This entailed the development, transfer, and promotion of sustainable market oriented technologies broadly defined as “technologies that respond to a market opportunity, are developed at the behest of and with potential users, based on previous market experience, and are economically viable in a significant number of market settings”. During the period from 2004 to 2007, the network implemented projects based on the recommendations of the workshop that discussed the subsector analysis that was commissioned during the second phase. The subsector analysis provided a comprehensive database, identified opportunities, constraints, and needs, and proposed areas for technological, institutional, organizational, and policy interventions. The outcome of the workshop developed the priority setting exercise which influenced the network’s activities. Germplasm development remained one of the major core activities of the network. More efforts were made to develop germplasm that responded to the emerging markets needs. Exchange and capacity building were increased. Germplasm from different sources was used, either as exotic or local seeds from crossing blocks or half-sib seeds collected from local cultivars to plant seedlings trials. A total of 869 families were planted at Namulonge and Serere Research Stations during the period. From these seedlings, the clones selected were advanced in clonal evaluation and in preliminary yield trials from which the national agricultural; research systems (NARS) continued to receive advanced germplasm for further evaluation in their respective agro-ecologies. Cassava is known primarily to have white roots. Cassava with yellow roots and enhanced β-carotene content has been grown by smallholder farmers for centuries with varying levels of importance in different cassava growing regions. IITA’s cassava breeders began working early on yellow root cassava with the selection and testing of improved yellow root clones. In East Africa, EARRNET took the lead in collaboration with Ugachick Poultry Breeders Ltd in testing the potential of incorporating cassava into animal feeds (for broiler chickens) with the objective of replacing a reasonable 10–20% of maize with cassava in feed formulations. This collaboration included screening yellow genotypes for multiple resistance, particularly to cassava mosaic disease (CMD) and the new threat, cassava brown streak disease (CBSD). From a total of 18 genotypes selected from yellow cassava trials in Namulonge, only two genotypes had a foliar CBSD index score above 20, namely MH05/0309 and MM98/1790. The genotype MM98/1790 also had severe CBSD root symptoms (score 4.5). Another genotype, MH04/2990, had no foliar CBSD symptoms but showed root symptoms (score 2.7). The rest showed good resistance to both CMD and CBSD. With the spread of CBSD into high altitude environments, contrary to what was known to be the ecology of the disease (low land along the coast of East and Southern Africa), more efforts were initiated by screening for CBSD the improved CMD resistant IITA/EARRNET midaltitude germplasm that were in in situ conservation. Additional seeds with a background from Amani (a research station in Kenya) materials were introduced for evaluation under high disease pressure areas in Mukono district in Uganda. After 4 years of intensive screening, potential resistant/tolerant genotypes were identified with good agronomic characteristics and preferred by farmers. These 50 genotypes were then challenged to CBSV infection through grafting.